HUBUNGANMOTOR ABILITY DENGAN KECEPATAN MENGGIRING BOLA PADA SISWA PUTRA EKSTRAKULIKULER SD SMP NEGERI SATAP 1 LINGSAR TAHUN 2015 - I Putu Beny Wiradarma; Lalu Hulfian; Isnaini Isnaini (Gelora : Jurnal Pendidikan Olahraga dan Kesehatan IKIP Mataram, 2016)
This research aimed to know there is or no correlation of speed (speed run 50 meters) and liveliness (zig-zag run) with speed dribble at extracurricular student of SD SMPN Satap 1 Lingsar in year 2015. Sample of this research used population study consist of 20 people. The  method  of  this  research used  experimental  design  with  multiple correlation design. Instrumental of this research used motor ability test (speed run 50 meters and zig zag run) and speed dribble test. The data analysis used r-test. Based on the result of data analysis showed  that  r-test  was  0,975.  The  conclusion  of  this  research  showed  that  correlation between there variables was very strong.